THE ROLE OF PARENTING IN LIMITING THE RISK OF NEGATIVE EFFECTS OF THE AUD SOCIAL ENVIRONMENT IN KB/RA BINA MUTIARA HATI SEMARANG - Qurrota Ayun; Muslam (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to investigate the role of parental parenting in limiting the negative influence of the social environment on early childhood development. The background of this research departs from the phenomenon of increasing the negative influence of the social environment that can have an impact on children's behavior and social development. The purpose of the study was to analyze the influence of various parenting models, namely permissive, authoritarian, and democratic, on children's social resilience. The method used is a descriptive qualitative approach with data collection through in-depth interviews and direct observation of parents and children at KB/RA Bina Mutiara Hati Semarang on October 1 – November 10, 2025. The results of the study show that democratic parenting is more effective in forming children's social resilience to negative environmental influences, while permissive and authoritarian parenting is less optimal in achieving it. These findings highlight the importance of a parenting approach that involves two-way communication and mutual understanding in shaping a child's character. The novelty of this research lies in the emphasis on the function of parenting as a protection against negative social influences that have not been explored much in the previous literature.